“Something is wrong!” A qualitative study of racial disparities in parental experiences of OSA detection in their child - Chung, Alicia; Farquharson, Leone; Gopalkrishnan, Akila; Honaker, Sarah Morsbach (Frontiers in Sleep, 2023)
Introduction: Approximately 3% of American children are affected by obstructive sleep apnea (OSA), yet Black children are 2-4 times more likely to experience OSA compared to White children. Little is known about parental experiences in detection, diagnosis, and treatment of OSA in their child, and how these experiences may differ by race. The study objective was to highlight convergent and divergent experiences between and across Black and White parents in the OSA detection process for their child.We conducted 27 semi-structured interviews with mothers whose child was referred for a diagnostic overnight polysomnogram (PSG) to assess for OSA. Parents described how their child was referred for a PSG and their perceptions and feelings throughout the detection process. Data were analyzed using a thematic descriptive approach. Frequency of themes were examined by race. Themes that were unique to one racial group were categorized as divergent, whereas themes described by individuals from both groups were categorized as convergent. Within the convergent themes, we examined the prevalence within each racial group, noting those that were more prevalent (>10% difference in prevalence) in one race or the other.The sample included 19 Black and 8 White mothers, who were 36 years old on average. Qualitative analysis yielded 21 themes across 5 categories that captured divergent and convergent experiences across Black and White mothers during the OSA detection process for their child. Divergent themes that were unique to Black mothers included It Takes a Village -Teacher, Misplaced Blame, Missing the Day/night Connection, Trust in Provider, and the belief that Snoring is Normal. Only one divergent theme among White parents emerged, worries about Dying in Ones Sleep. Additional convergent themes were identified that were more prevalent in one race compared to the other.Discussion: Black and White mothers experienced different paths to detection and diagnosis for their child's sleep disordered breathing, that are affected by individual awareness, education, patientprovider interactions, and experiences with the healthcare system. Divergent themes such as Misplaced Blame among Black mothers were a potential indication of racism and health disparities.